Vasodilators for women undergoing fertility treatment - Gutarra‐Vilchez, Rosa B. (2018)
Background: The rate of successful pregnancies brought to term has barely increased since the first assisted reproductive technology (ART) technique became available. Vasodilators have been proposed to increase endometrial receptivity, thicken the endometrium, and favour uterine relaxation, all of which could improve uterine receptivity and enhance the chances for successful assisted pregnancy. Objectives: To evaluate the effectiveness and safety of vasodilators in women undergoing fertility treatment. Search methods: We searched the following electronic databases, trial registers, and websites: the Cochrane Gynaecology and Fertility Group (CGF) Specialised Register of controlled trials, the Cochrane Central Register of of Controlled Trials, via the Cochrane Register of Studies Online (CRSO), MEDLINE, Embase, PsycINFO, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Knowledge, the Open System for Information on Grey Literature in Europe (OpenSIGLE), the Latin American and Caribbean Health Science Information Database (LILACS), clinical trial registries, and the reference lists of relevant articles. We conducted the search in October 2017 and applied no language restrictions. Selection criteria: Randomised controlled trials (RCTs) comparing vasodilators alone or in combination with other treatments versus placebo or no treatment or versus other agents in women undergoing fertility treatment. Data collection and analysis: Four review authors independently selected studies, assessed risk of bias, extracted data, and calculated risk ratios (RRs). We combined study data using a fixed-effect model and assessed evidence quality using Grades of Recommendation, Assessment, Development and Evaluation Working Group (GRADE) methods. Our primary outcomes were live birth or ongoing pregnancy and vasodilator side effects. Secondary outcomes included clinical pregnancy, endometrial thickness, multiple pregnancy, miscarriage, and ectopic pregnancy. Main results: We included 15 studies with a total of 1326 women. All included studies compared a vasodilator versus placebo or no treatment. We judged most of these studies as having unclear risk of bias. Overall, the quality of evidence was low to moderate for most outcomes. The main limitations were imprecision due to low numbers of events and participants and risk of bias due to unclear methods of randomisation.Vasodilators probably make little or no difference in rates of live birth compared with placebo or no treatment (RR 1.18, 95% confidence interval (CI) 0.83 to 1.69; three RCTs; N = 350; I² = 0%; moderate-quality evidence) but probably increase overall rates of side effects including headache and tachycardia (RR 2.35, 95% CI 1.51 to 3.66; four RCTs; N = 418; I² = 0%; moderate-quality evidence). Evidence suggests that if 236 per 1000 women achieve live birth with placebo or no treatment, then between 196 and 398 per 1000 will do so with the use of vasodilators.Compared with placebo or no treatment, vasodilators may slightly improve clinical pregnancy rates (RR 1.45, 95% CI 1.19 to 1.77; 11 RCTs; N = 1054; I² = 6%; low-quality evidence). Vasodilators probably make little or no difference in rates of multiple gestation (RR 1.15, 95% CI 0.55 to 2.42; three RCTs; N = 370; I² = 0%; low-quality evidence), miscarriage (RR 0.83, 95% CI 0.37 to 1.86; three RCTs; N = 350; I² = 0%; low-quality evidence), or ectopic pregnancy (RR 1.48, 95% CI 0.25 to 8.69; two RCTs; N = 250; I² = 5%; low-quality evidence). All studies found benefit for endometrial thickening, but reported effects varied (I² = 92%) and ranged from a mean difference of 0.80 higher (95% CI 0.18 to 1.42) to 3.57 higher (95% CI 3.01 to 4.13) with very low-quality evidence, so we are uncertain how to interpret these results. Authors' conclusions: Evidence was insufficient to show whether vasodilators increase the live birth rate in women undergoing fertility treatment. However, low-quality evidence suggests that vasodilators may slightly increase clinical pregnancy rates. Moderate-quality evidence shows that vasodilators increase overall side effects in comparison with placebo or no treatment. Adequately powered studies are needed so that each treatment can be evaluated more accurately.